AI-Powered Systems for Automated Detection and Classification of Medicinal Plants - Sreedhanya C; Rathi B; Anjali T C (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Medicinal plants have been widely used for traditional and modern healthcare due to their therapeutic properties. Identifying medicinal plants correctly is crucial for their effective utilization. This paper presents an Android application that detects whether a plant is medicinal or not using Convolutional Neural Networks (CNN).The system allows users to upload an image of a plant, which is transformed using a CNN- based deep learning model trained on a Data repository of medicinal and non-medicinal plant images. The model classifies the plant based on its features and provides real-time critique to the user.The application is designed to be lightweight and efficient, ensuring fast and accurate classification. The CNN model is either embedded within the app using TensorFlow Lite or processed through a cloud-based back end for enhanced effectiveness. This project aims to assist researchers, botanists, and herbal medicine enthusiasts in fostering medicinal plants with ease.